CmVPS41 Is a General Gatekeeper for Resistance to Cucumber Mosaic Virus Phloem Entry in Melon - Pascual, Laura; Yan, Jinqiang; Pujol, Marta; Monforte, Antonio J.; Picó, Belén; Martín-Hernández, Ana Montserrat (Frontiers in Plant Science, 2019)
Melon production is often compromised by viral diseases, which cannot be treated with chemicals. Therefore, the use of genetic resistances is the main strategy for generating crops resistant to viruses. Resistance to Cucumber mosaic virus (CMV) in melon is scarce, described in few accessions. Until recently the only known resistances accessions were Freeman's cucumber and PI 161375, cultivar Songwhan Charmi (SC). Resistance to CMV in melon is recessive and generally oligogenic and quantitative. However, in SC, the resistance to CMV strains of subgroup II (SGII) is monogenic, depending only on one gene, cmv1, which is able to stop CMV movement by restricting the virus to the bundle sheath (BS) cells and preventing a systemic infection. This restriction depends on the viral movement protein (MP). Chimeric viruses carrying the MP of SGII strains, like CMV-LS are restricted in the BS cells, whereas those carrying MP from subgroup I (SG I), like CMV-FNY, are able to overcome this restriction. cmv1 encodes a Vacuolar Protein Sorting 41 (CmVPS41), a protein involved in the transport of cargo proteins from the Golgi to the vacuole through late endosomes. We have analyzed the variability of the gene CmVPS41 in a set of 52 melon accessions belonging to all melon groups, both from the spp melo and the spp agrestis. We have identified 16 different haplotypes, encoding 12 different CmVPS41 proteins. Challenging members of all haplotypes with CMV-LS, we have identified nine new resistant accessions. The resistance correlates with the presence of two mutations, either L348R, previously found in the accession SC and present in other three melon genotypes, or G85E, present in Freeman's cucumber and found also in four additional melon genotypes. Moreover, the new resistant accessions belong to three different melon horticultural groups, Conomon, Makuwa and Dudaim. In the new resistant accessions, the virus was able to replicate and move cell-to-cell, but was not able to reach the phloem. Therefore, resistance to phloem entry seems to be a general strategy in melon controlled by CmVPS41. Finally, the newly reported resistant accessions broaden the possibilities for the use of genetic resistances in new melon breeding strategies.